2018
DOI: 10.1089/neu.2017.5280
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2/E1B-19KD-Interacting Protein 3/Light Chain 3 Interaction Induces Mitophagy in Spinal Cord Injury in Rats BothIn VivoandIn Vitro

Abstract: Autophagy and mitophagy have been shown to occur in spinal cord injury (SCI). Bcl-2/E1B-19KD-interacting protein 3 (BNIP3) and its homologue, NIX, have been implicated in the regulation of mitophagy. The aim of this work was to characterize the mechanisms and role of BNIP3 in SCI-associated mitophagy. Our data showed that BNIP3, targeted to mitochondria, interacted with microtubule-associated protein 1A/1B-light chain 3 (LC3), which is targeted to autophagosomes, thus forming a mitochondria-BNIP3-LC3-autophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Mitophagy is a quality control process: damaged, depolarized mitochondria are removed, thereby limiting the generation of reactive oxygen species (ROS) and release of apoptogenic factors and blocking cell death (e.g. Wang et al, 2017;Qiao et al, 2016;Yu et al, 2018b;Di Rita et al, 2018;Li et al, 2018). However, mitophagy is only beneficial to the cells if it occurs in a limited and regulated manner, and its over-activation can be lethal, as outlined below.…”
Section: Death From Over-eatingelimination Of Intracellular Organellementioning
confidence: 99%
See 2 more Smart Citations
“…Mitophagy is a quality control process: damaged, depolarized mitochondria are removed, thereby limiting the generation of reactive oxygen species (ROS) and release of apoptogenic factors and blocking cell death (e.g. Wang et al, 2017;Qiao et al, 2016;Yu et al, 2018b;Di Rita et al, 2018;Li et al, 2018). However, mitophagy is only beneficial to the cells if it occurs in a limited and regulated manner, and its over-activation can be lethal, as outlined below.…”
Section: Death From Over-eatingelimination Of Intracellular Organellementioning
confidence: 99%
“…Hypoxia has been shown to induce mitophagy in cultured spinal cord neurons (Yu et al, 2018a). Knockdown of Bcl-2/E1B-19KDinteracting protein 3 (BNIP3), which recruited LC3 (also known as MAP1LC3) to the mitochondria, blocked mitophagy and restored declining ATP levels and cell viability following hypoxia.…”
Section: Death From Over-eatingelimination Of Intracellular Organellementioning
confidence: 99%
See 1 more Smart Citation
“…The BHRF1 protein (a BCL2 homolog) is one of the autophagic receptors that can induce mitochondrial fission and degradation, thus resisting innate immunity activation (Vilmen et al, 2020). However, another study shows the damaging role of BHRF1 within hypoxia brain and spinal cord injury (Shi et al, 2014;Yu et al, 2018). Unraveling these specific roles further could facilitate and identify possible therapeutic targets.…”
Section: Mitophagymentioning
confidence: 99%
“…This last type is predominant in the hippocampus, where the loss of adult stem neurons, consequent to insulin withdrawal, induces cognitive deficits ( Yu et al, 2008 ; Jung et al, 2020 ). Moreover, also selected autophagy of mitochondria, called mitophagy, whenever excessive becomes detrimental leading to neuronal death, such as reported in ischemic and hypoxic events in vitro and in rat spinal cord ( Feng et al, 2018 ; Yu et al, 2018 ). Recent studies in preclinical animal models and in post-mortem brain samples from patients indicated a strict connection between defective autophagy and mitophagy to the pathogenesis of Parkinson’s ( Gao et al, 2017 ; Arotcarena et al, 2019 ; Lin et al, 2019 ) and Alzheimer’s disease ( Chakravorthy et al, 2019 ; Xie et al, 2020 ).…”
Section: Autophagic Signalingmentioning
confidence: 99%